Forensic Construction Investigation of Reconstructed Premises - I. D. Platonova; N. G. TSaritova; E. G. Tekutov (Теория и практика судебной экспертизы)
The article addresses solving the issue of the possibility of preserving reconstructed premises or carrying out proposed reconstruction works in the course of in the course of construction forensic investigation. The significance of the problem attributes to the volume of the stock of residential and public buildings which are older than 40 years (according to statistics, the housing stock of Russia in 1980 was 1,861 million m2 , in 2015 – 3,581 million m2 ), outdated layouts of premises, and the evolved consumers’ idea of comfort.A construction expert’s task is to determine if there is a possibility to change the layout, the function of premises to improve living conditions, or reconstruction poses a threat to the state of the object, its further proper operation, the integrity of the installed engineering systems, the appearance of the facades, nearby buildings and structures. Using regulatory material, the authors consider the criteria for solving this problem, present the procedure for conducting studies of buildings or structures, building materials, structures, and relevant documents in this line of forensic construction examination. Finally, the article gives specific examples of the redevelopment of apartments, a proposed reconstruction of the kindergarten premises.It is noted that the reliability of experts’ opinions is based on a comprehensive, unbiased analysis of all the technical and economic characteristics of construction objects, verification of documentation, an inspection of structures for compliance with the requirements of federal laws, rules, and regulations.